ФОРМОУТВОРЕННЯ МОНОКРИСТАЛІВ АЛМАЗУ ПРИ ЗМІНІ КОНФІГУРАЦІЇ РЕЗИСТИВНОЇ СИСТЕМИ НАГРІВУ В АПАРАТАХ ВИСОКОГО ТИСУ КУБІЧНОГО ТИПУ - Лисаковський, Валентин; Івахненко, Сергій; Бурченя, Андрій; Коваленко, Тетяна; Стрельчук, Віктор; Ніколенко, Андрій; Іванченко, Сергій; Марченко, Антон (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2024)
The limiting values of axial and radial temperature gradients for growing diamond single crystals of different types and habit have been calculated and experimentally studied. Defined temperature limit values, exceeding which leads to the growth of defective crystals; it is shown that such values differ for each solution-melt system and must be selected separately. The necessary temperature conditions for the formation of cubic and cuboctahedral diamond single crystals have been established, as well as the prevention of the formation of binary crystals with the development of a defective region of the crystal associated with a change in the characteristics of carbon transfer from the source to the crystallization front.